A Prospective Drug Utilisation Study and Pharmacoeconomic Analysis in Paediatric Dentistry at a Tertiary Hospital - Shrestha, Binaya; Pradhan, Megha (Medical Journal of Shree Birendra Hospital, 2020)
Introduction: Paediatric dentistry is the branch of dentistry dealing with children from birth to adolescence. Children tend to suffer from various dental conditions which can be primarily infective in nature and hence requires drugs that can be expensive. Drug utilisation data are needed for developing and monitoring policies because data on drug expenditure are not sufficient. Methods: This was a prospective cross-sectional study conducted in the Department of Pedodontics (paediatric dentistry) of a tertiary care teaching institute in Kathmandu, Nepal from July 2019 to December 2019. During the study period a total of 200 prescriptions were collected. Analysis was conducted using MS excel 2016 and further required analysis was done using Statistical Package for the Social Sciences v22.0. Results: A total of 200 prescriptions were analysed during the study period, of which 126 were males whereas 74 were females. The most common drug prescribed was paracetamol whereas amoxicillin was the most commonly prescribed antibiotics. Most common condition was periapical abscess but space infection was the most expensive condition.There was no statistically significance between the cost of drugs prescribed for the male and female patients. Conclusions: The drug prescription pattern was found to be rational. Every institution must have their own Drugs and Therapeutics Committee as has been suggested by WHO, so that patients will be benefited through decreasing economical burden, and adverse drug reactions and that by this, therapeutic effect will be increased.